2017
DOI: 10.5301/tj.5000683
|View full text |Cite
|
Sign up to set email alerts
|

Dicentric Translocation (9;12) in Acute Lymphoblastic Leukemia: A Chromosomal Abnormality with an Excellent Prognosis?

Abstract: Given the excellent results of our patient and most of the series published to date, an international study is necessary to determine the true prognostic significance of this molecular alteration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
1
0
0
Order By: Relevance
“…9 Illade et al reported a 14-year-old male with t(9;12)(p13;p13), who was in remission on 4-year follow-up. 14 In concordance with these studies, we observed overall survival of 67% for 3 years ( Fig. 4 ).…”
Section: Discussionsupporting
confidence: 90%
“…9 Illade et al reported a 14-year-old male with t(9;12)(p13;p13), who was in remission on 4-year follow-up. 14 In concordance with these studies, we observed overall survival of 67% for 3 years ( Fig. 4 ).…”
Section: Discussionsupporting
confidence: 90%